(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The present study describes a low cost infrared device developed to establish rats’ nose poking responses. The infrared device was easily adapted to operant chamber and detected nose poking responses that were emitted in the same location as used for the antecedent stimuli. Acquisition of a simple successive discrimination between one intermittent sound and one continuous sound was analyzed using this device. The results suggested that the infrared device was an effective operandum for establishing auditory simple successive discriminations in rats. Future studies should verify if discriminations that are more complex could be established in rats with this kind of device.